2017
DOI: 10.1016/s1474-4422(16)30346-5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular function in presymptomatic and symptomatic individuals with hereditary cerebral amyloid angiopathy: a case-control study

Abstract: Summary Background Previous work suggests that impairments of cerebrovascular flow or reactivity might be early markers of cerebral amyloid angiopathy (CAA). Hereditary cerebral hemorrhage with amyloidosis–Dutch type (HCHWA-D) is a genetic form of CAA that can diagnosed early by DNA testing, allowing study of CAA before onset of clinical symptoms. The aim of the present study was to investigate whether hemodynamic measures are decreased in HCHWA-D mutation carriers compared to healthy controls. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(121 citation statements)
references
References 21 publications
9
112
0
Order By: Relevance
“…(37) Van Opstal et al (n=60) demonstrated BOLD reactivity in the occipital cortex is reduced in individuals with symptomatic hereditary cerebral amyloid angiopathy who had severe WMH and microbleeds compared to controls and presymptomatic carriers. (38)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(37) Van Opstal et al (n=60) demonstrated BOLD reactivity in the occipital cortex is reduced in individuals with symptomatic hereditary cerebral amyloid angiopathy who had severe WMH and microbleeds compared to controls and presymptomatic carriers. (38)…”
Section: Discussionmentioning
confidence: 99%
“…(4, 23) Studies of SVD mechanisms and potential interventions should consider using measures of dynamic vascular function such as CVR or pulsatility rather than resting CBF. (5, 38)…”
Section: Discussionmentioning
confidence: 99%
“…In the cortical gray matter, which may be less susceptible to ischemia because of a richer network of collateral vessels than the white matter, intermittent reduction in blood flow could nonetheless lead to microinfarction. Alterations in vascular reactivity appear early in CAA and are progressive (Switzer et al 2016;van Opstal et al 2017). A study of presymptomatic Dutch CAA mutation carriers found that they exhibited abnormal functional magnetic resonance imaging responses at an early stage of disease, prior to the onset of symptomatic hemorrhages, cognitive impairment, or neuroimaging evidence of brain atrophy (van Opstal et al 2017).…”
Section: Non-ad Pathomechanisms Of Neurodegeneration In Caamentioning
confidence: 99%
“…Alterations in vascular reactivity appear early in CAA and are progressive (Switzer et al 2016;van Opstal et al 2017). A study of presymptomatic Dutch CAA mutation carriers found that they exhibited abnormal functional magnetic resonance imaging responses at an early stage of disease, prior to the onset of symptomatic hemorrhages, cognitive impairment, or neuroimaging evidence of brain atrophy (van Opstal et al 2017). Thus, impaired vasodilation precedes evidence of neurodegeneration and may cause it.…”
Section: Non-ad Pathomechanisms Of Neurodegeneration In Caamentioning
confidence: 99%
“…The amplitude of the functional MRI response to visual stimulation is reduced not only in symptomatic carriers who had already suffered CAA-related bleeding, but even in presymptomatic mutation carriers without prior hemorrhage. 33 These results point squarely to vascular reactivity as an early step in CAA pathogenesis and thus a candidate target for early intervention strategies.…”
Section: Links Between Cerebral Small Vessel Disease and Dementia: Lementioning
confidence: 98%